EFFECT OF THE TiBN COATING ON A HSS DRILL WHEN DRILLING THE MA8M Mg ALLOY - Karaca, Faruk; Aksakal, Bunyamin (Inst Za Kovinske Materiale I in Tehnologie, 2016)
Mg alloy MA8M is used in the aerospace and food industries and in biomedical applications due to its lightness and biocompatibility. This paper presents the drilling performance of the standard HSS and TiBN-coated drill bits during the machining of the MA8M Mg alloy at various drill rotational speeds and feed rates. After the experiments, the surface roughness, topography and chip formation were analyzed. Atomic-force microscopy (AFM) and surface profilometer were used for this purpose. It was observed that higher drilling feed rates and drill rotational speeds lead to lower surface-roughness values. TiBN-coated drill bits exhibited undesired surface qualities.
Keywords: MA8M Mg alloy; TiBN coating; twist drills; surface quality; multiple regression analysis; chip formation